2015
DOI: 10.1002/cphc.201500416
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Dynamics Mechanism of Charge Separation in the Initial‐Stage Dynamics of Photoinduced Water Splitting in XMnWater (X=OH, OCaH) and Electron–Proton Acceptors

Abstract: An electron dynamics mechanism of charge separation in the initial stage of excited-state reactions of the class of XMnOH2 ⋅⋅⋅A${ \to }$XMnOH⋅⋅⋅HA (X=OH or OCaH; A=N-methylformamidine, guanidine, imidazole, or ammonia cluster) is reported. The dynamic effect of calcium doping is also revealed. This study provides a novel factor to be considered in designing efficient systems for photoinduced water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The EPDs of these types were also studied extensively in our previous study, [2] through which we revealed the roles of doped Ca atoms, which 1) suppress the annihilation process of the created charges eparation in the EPA, and 2) modulate the channels of the pathway of electron flow. [1,2] Here, we therefore examined whether these are actually true of the Y-shaped acceptor.S ystemsA1a nd A2 have been designed to be small enought oa llow us to perform fulldimensional nonadiabatic electron dynamics. The EA (H T1 OÀ C 6 H 4 ÀNH 3 + )a nd PA ([C 3 N 2 H 3 ] À )c omponents are used both in systemsA1a nd A2.…”
Section: Systems Of the Proton-electron Donors And Acceptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The EPDs of these types were also studied extensively in our previous study, [2] through which we revealed the roles of doped Ca atoms, which 1) suppress the annihilation process of the created charges eparation in the EPA, and 2) modulate the channels of the pathway of electron flow. [1,2] Here, we therefore examined whether these are actually true of the Y-shaped acceptor.S ystemsA1a nd A2 have been designed to be small enought oa llow us to perform fulldimensional nonadiabatic electron dynamics. The EA (H T1 OÀ C 6 H 4 ÀNH 3 + )a nd PA ([C 3 N 2 H 3 ] À )c omponents are used both in systemsA1a nd A2.…”
Section: Systems Of the Proton-electron Donors And Acceptorsmentioning
confidence: 99%
“…In our previous studies, we have conceived aq uantum mechanical mechanism of charge separation by Mn oxides, [1,2] which can be summarized as follows [Eq. (2)]:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Nagashima and Takatsuka reported recently a description of proton transfer in an excited state of phenol in ammonia and showed an orbital with strong Rydberg character playing a critical role in the reaction, suggesting that this findings calls for a novel fundamental description of excited state proton transfer. We believe that the MOA analysis will capture the change in orbital character along the reaction pathway, and provide a quantitative description of orbital interactions that come into play …”
Section: Discussionmentioning
confidence: 99%